NURS-17. PROSPECTIVE SYMPTOM ASSESSMENT IN CHILDREN WITH PROGRESSIVE BRAIN TUMORS. Issue 2 (22nd June 2018) - Gilger, Elizabeth; Hemenway, Molly; Raybin, Jennifer; Balian, Chelsea; Ward, Jessica; Montgomery, Kathleen
Abstract: BACKGROUND: Children with brain tumors may have unique symptoms at end of life (EOL) compared to other cancers. Most of the pediatric oncology literature regarding symptoms during palliative care or EOL is retrospective. OBJECTIVE: The study purpose was to prospectively describe symptom frequency, severity, and distress level in children/adolescents with advanced cancer using patient self-report and parent proxy. A data subset of subjects with brain tumors was analyzed. DESIGN: The multi-institutional study used a prospective cohort design. Eligibility included 7-18 years, English-speaking, and advanced cancer diagnosis (2-week history of progressive, recurrent, non-responsive disease, or a decision not to pursue curative-focused therapy). A modified Memorial Symptom Assessment Scale (MSAS) version was used. Symptoms were measured electronically biweekly. Disease status and current treatment were recorded. Data was analyzed using descriptive statistics and univariate logistic regression analysis. RESULTS: Out of 47 patient/parent dyads, 15 [WJ1] had a brain tumor. The most frequently reported symptoms by all subjects were pain (n=195/562, 34.70%), lack of energy (n=186/561, 33.16%), and nausea (n=156/560, 27.86%). However, children with brain tumors reported fatigue (94/185=50.81%), irritation (n=43/130, 33.08%), and pain (n=61/185, 32.97%) most frequently. Disease presence (P=0.0006), recent disease progression (P=0.029), [WJ2] receiving cancer therapy (P=0.0045), and high intensity cancer therapy (P=0.0822) were significant factors related to fatigue. CONCLUSIONS: Collecting symptom assessment data prospectively in this population is feasible. Although pain was the most frequently reported symptom overall, fatigue and irritability were more prevalent in brain tumor patients. This finding warrants further investigation and potential intervention.